استخدام تحليل "database Dimensions " لاستكشاف مجالات البحث المشترك - طباخي ،سناء; بكوش ،لطيفة (جامعة الوادي University of Eloued, 2024)
This study aims to attempt to identify recent trends in the development and vision of research horizons in the fields of joint research between organizational ambidexterity, management accounting and entrepreneurial orientation by conducting a bibliometric analysis of the research indexed on this topic in Dimensions database during the period 2014 to 2023. The extracted data was analyzed and using the studied database analysis, in examining publications through the joint presence of keywords in the title and abstract. The analysis is performed using frequencies and citation analysis. The results provided an overview of the trends in scientific studies on the subject, which showed the scarcity, modernity, and fluctuation of published research in this field within Dimensions database, which creates research gaps that will be the focus of future research. This study may be a guidance tool for researchers working in a similar field. They can also obtain insights into the sector that should be considered for further study, such as quantitative analysis, and know the importance of the practical relationship between organizational ambidexterity, management accounting, and entrepreneurial orientation after showing theoretical features about it in this study
Using "Database Dimensions" analysis to explore areas of joint research between organizational ambidexterity, management accounting and entrepreneurial orientation
Keywords: البراعة التنظيمية; المحاسبة الإدارية; التوجه الريادي; الفجوة البحثية; Organizational Ambidexterity; Management Accounting; Entrepreneurial Orientation; Research Gap.